Metode dan Paradigma Pemahaman Hadis di Indonesia - Ari Rustianto, Muhammad; Pribadi, Guntur; Andaryuni, Lilik (Attractive : Innovative Education Journal, 2024)
Changes and developments over time have encouraged the importance of contextual understanding of hadith by the people. In the midst of this, studying the understanding of hadith using a methodical approach has urgency, especially its position as a source of law after the Koran and its function as mubayyin (explainer). In Indonesia, the understanding of hadith can be seen as still experiencing delays. The aim of this research is to explain the methods and understanding of hadith in Indonesia. This research method uses a library research approach, namely by conducting a study of several literatures related to hadith studies studied and developed in Indonesia, including several Islamic intellectual scientific works that examine hadith studies in Indonesia. The findings show that in Indonesia there are several popular methods of understanding hadith that are studied and studied in hadith science literature, including the tahlili (analytical) method, the ijmali (global) method, the muqarin (comparative) method, and the maudhu'i method ( thematic). It is possible that the models of methods for understanding hadith will experience development as times change. The problem of modern life like today, of course, is that understanding hadith requires an understanding that can respond to the needs of the times. In the current context, for example, understanding hadith using a scientific and philosophical approach has become a model of approach that is seen as being able to respond to modernity. It is hoped that this approach model can provide a comprehensive understanding of the hadiths of the Prophet SAW, that is, not only to be understood at a textual level, but also to be understood contextually and substantively so that the essence and wisdom behind the hadith texts can be understood wisely. Keywords: Understanding of Hadith, Hadith Studies In Indonesia